2021
DOI: 10.25133/jpssv302022.014
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity and Healthcare Utilization in Indonesia: Evidence from Indonesian National Household Surveys

Abstract: Treatment for sicknesses in healthcare is a crucial determinant to improve health. In Indonesia, the unmet need for healthcare is common for people in the lower economic group. This study aims to examine how food insecurity affects outpatient care using the indicators of food insecurity to highlight individuals with high health risks and experiencing problems with limited resources. The data used in this study consisted of 159,236 individuals representing different age ranges from the 2017 National Socio-Econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Household surveys are the primary data source for studying living standards, inequality, and financial or social protection (Attia-Konan et al 2019; Brinda et al 2015; Sari and Handayani 2022; Van Minh et al 2013; Zeng et al 2018). They are mostly cross-sectional and consequently use questions with retrospective reference periods ranging up to one year (Browning et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Household surveys are the primary data source for studying living standards, inequality, and financial or social protection (Attia-Konan et al 2019; Brinda et al 2015; Sari and Handayani 2022; Van Minh et al 2013; Zeng et al 2018). They are mostly cross-sectional and consequently use questions with retrospective reference periods ranging up to one year (Browning et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings have been shown in low-and middle-income countries. In Indonesia, for example, food insecurity was also observed as a risk of restricted access to modern health care for outpatient care [9]. Research also shows in the Democratic Republic of Congo that the odds of adhering to antiretroviral therapy were lower among patients with food insecurity in comparison to those without any food insecurity [10].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that food insecurity leads to increased medical expenditure and greater use of acute care services among children [ 19 , 20 ], older adults [ 17 , 21 ], and individuals with chronic conditions [ 22 ]. On the other hand, several studies have reported reduced outpatient visits and lower access to modern healthcare in food insecure populations [ 20 , 23 , 24 ]. In South Korea (Korea, hereafter), where healthcare provision is universal, food insecure individuals can access primary and routine care at an affordable rate, but they may encounter financial barriers to advanced medical services that require significant co-payments or out-of-pocket expenses [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%